(n, n(n‐1), n‐1) Permutation group codes. Issue 9 (11th April 2016) - Peng, Li
Abstract : Two different subgroups C n and L n of symmetric group S n are first designed and then to construct a family of permutation group codes P n with code length n, minimum Hamming distance n − 1, cardinality n ( n − 1) and error‐correcting capability n − 2 is composited.